Verbalizing Situation Types: A Comparative Study of English and Arabic (Journal of the College of Basic Education, 2025)
This study explores the linguistic realizations of situation types in English and Arabic, aiming to bridge a gap in cross-cultural pragmatics by examining how each language encodes social interactions such as apologies, compliments, requests, and expressions of gratitude. The research addresses the question of how cultural norms influence the verbal expression of these acts in both languages. The primary objective is to identify patterns of variation in the structure and strategy of speech acts across cultures. The data were collected from naturally occurring conversations in media texts and online discourse and analyzed using Brown and Levinson’s (1987) Politeness Theory as a model of analysis. The findings indicate that Arabic speakers frequently employ indirect, formal, and rhetorically rich expressions, especially in contexts that demand deference or emotional depth, while English speakers favor direct and concise formulations aimed at communicative efficiency. These conclusions highlight the importance of considering cultural context in language use and provide insights that are essential for translation, language education, and intercultural communication.